Evaluation of the Efficacy of PARP Inhibitors in Metastatic Castration-Resistant Prostate Cancer: A Systematic Review and Meta-Analysis - Wu, Kan; Liang, Jiayu; Shao, Yanxiang; Xiong, Sanchao; Feng, Shuyang; Li, Xiang (Frontiers in Pharmacology, 2021)
Background: Poly (ADP-ribose) polymerase (PARP) inhibitors have breakthrough designations for metastatic castration-resistant prostate cancer (mCRPC). We performed a meta-analysis of current clinical trials to evaluate the efficacy of PARP inhibitors in patients with mCRPC based on their genetic status. Methods: On August 2020, PubMed, Scopus, Embase, Cochrane Central Register of Controlled Trials, and Web of Science were searched for phase II/III clinical studies on PARP inhibitors in mCRPC patients. Data were extracted independently by two investigators and analyzed using Review Manager software version 5.3. Primary endpoints included overall response rate (ORR) and progression-free survival (PFS). Results: Nine clinical trials were identified and analyzed for the clinical benefit of PARP inhibitors in mCRPC patients (n=1219). Pooled analyses demonstrated that PARP inhibitors could provide a significant improvement of ORR and PFS in patients with homologous recombination deficiency (HRD) when compared to non-HRD patients. Within the HRD subgroup, the BRCA mutation patients achieved significantly higher ORR (odds ratio [OR]: 8.94, 95% confidence interval [CI]: 5.59–14.29) and PFS rates at 12 months (OR: 3.23, 95% CI: 1.71–6.10) when compared to BRCA wild-type patients. Furthermore, patients harboring HRD without BRCA mutations have a higher objective response after PARP inhibitor treatment, as compared to the non-HRD patients. Conclusions: PARP inhibitor is an effective treatment option for mCRPC patients with HRD mutation genes when compared to non-HRD patients. In addition to BRCA mutations, other HRD-related gene aberrations may also be used as novel biomarkers to predict the efficacy of PARP inhibitors.